Project-based Learning (PBL) in EFL learning: Lesson from Indonesia - Ngadiso Ngadiso; Teguh Sarosa; Muhammad Asrori; Nur Arifah Drajati; Anis Handayani (STAI Hubbulwathan Duri, 2021)
Project-based learning (PBL) has gained popularity in education recently. This teaching method provides opportunities for students to learn independently by doing group works in the form of a project. It is seen as a suitable method to teach EFL to replace the traditional ways of teaching. Thus, this case study explores the students' and teachers' experience implementing PBL in the EFL class. Three EFL classes from three different high schools in Indonesia were observed to explore this issue. Six students and three teachers were interviewed to confirm the observation’s result and determine their perception of learning using PBL. The findings show that the class situation improved positively after implementing PBL. Furthermore, PBL was well perceived by both students and teachers. The teaching and learning process went smoothly and well-controlled. The students and teachers show positive perceptions toward PBL in EFL classes. However, some negative points of PBL were also pointed out. Thus, educational sectors may use this study's results to improve the educational quality, specifically for EFL classes.